DECISION SUPPORT APPLICATION FOR DETERMINING THE AMOUNT OF PROCUREMENT OF GOODS USING THE FUZZY TSUKAMOTO METHOD BASED ON WEBSITE AT PT. SAKA MITRA USAHA - Anggoro Sakti; Dewiyani Sunarto; Agus Dwi Churniawan (Jurnal Sistem Informasi Universitas Dinamika, 2021)
PT. Saka Mitra Usaha is a national private company that is engaged in Human Resource Management Outsourcing services. Experienced, competent and knowledgeable professionals in the field of outsourcing services. This company is supported by experienced professionals in their fields, individuals who are trained, educated and have high dedication and always fulfill satisfaction for service users. The main problem in a company's warehouse is the accumulation of goods caused by more incoming goods. Another case is that the goods that come out are more of the goods that enter so that they have a bad impact on the goods which results in big losses for the company because they cannot meet the expenditure / expenditure of the goods at that time. The solution to be created is a web-based application that can determine the amount of goods produced. The process of predicting goods will use the Tsukamoto fuzzy method, this method is a way to map an input space into an output space. This method will be used to determine the prediction of the inventory of goods or the purchase of an item for inventory based on data on the amount of inventory remaining, purchase data and the number of goods out. These data are variables which will be represented by fuzzy functions. From this research, it produces a decision support application for inventory of goods that will be used by PT. SAKA MITRA USAHA to help managers determine the amount of procurement of goods in future warehouses, assist companies in determining goods production decisions, assist companies in mapping production of goods correctly and precisely through dashboard charts, forecasts of goods, and prediction reports.